2001
DOI: 10.1021/bi002101f
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structures and Integrin Binding Activities of an RGD Peptide with Two Isomers

Abstract: The Arg-Gly-Asp (RGD) sequence serves as the primary integrin recognition site in extracellular matrix proteins, and peptides containing this sequence can mimic the activities of the matrix proteins. Depending on the context of the RGD sequence, an RGD-containing peptide may bind to all of the RGD-directed integrins, to a few, or to only a single one. We have previously isolated from a phage-displayed peptide library a cyclic peptide that binds avidly to the alpha(v)beta3 and alpha(v)beta5 integrins but does n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
107
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(109 citation statements)
references
References 32 publications
2
107
0
Order By: Relevance
“…Turning our attention to polypeptide systems, six protein conformations (1PLW [45], 1FUL [46], 1RVS [47], 1EDW [48], 1FDF [49] and 1UBQ [50]) from the Brookhaven National Laboratory Protein Data Bank (PDB) [51] were used as starting configurations for our calculations. Table 1 shows the computed HOMO-LUMO gaps for these structures in vacuo, using the PBE functional.…”
Section: Protein Systemsmentioning
confidence: 99%
“…Turning our attention to polypeptide systems, six protein conformations (1PLW [45], 1FUL [46], 1RVS [47], 1EDW [48], 1FDF [49] and 1UBQ [50]) from the Brookhaven National Laboratory Protein Data Bank (PDB) [51] were used as starting configurations for our calculations. Table 1 shows the computed HOMO-LUMO gaps for these structures in vacuo, using the PBE functional.…”
Section: Protein Systemsmentioning
confidence: 99%
“…Also in this case, structure-activity relationship studies showed that a folded structure is necessary for activity. Although theoretical and NMR-based experimental studies showed the presence of turn geometry also in the RGD sequence, centered on the glycine residue, the extreme conformational freedom of RGD makes, in this case, the open structure more favorable (24,25). For this reason, the presence of conformational constraints is necessary to obtain the optimal geometry for receptor recognition, e.g.…”
Section: Figmentioning
confidence: 99%
“…RGD binds to five ␣V integrins (␣v␤1, ␣V␤3, ␣v␤5 ␣v␤6, and ␣v␤8), two ␤1 integrins (␣5 and ␣8), and ␣IIb␤3 (24). RGD in its disulfidebonded cyclic form (CDCRGDCFC) binds more strongly to integrins than does its linear form (25). RGD has been extensively studied in targeting and killing tumor cells (26).…”
mentioning
confidence: 99%